Intervensi Pemerintah Desa dalam Program Pembangunan Pertanian: Suatu Pendekatan Ekonomi Politik di Konteks UU Desa 2014 - Komang Ariyanto (Universitas Terbuka, 2022)
In the context of the 2014 Village Law, village government intervention in agricultural development is very important in improving the welfare of village communities. This study aims to determine the intervention of the village government on agricultural development programs and to find out the opportunities and limitations of the village government in agricultural development in the village. This research uses a qualitative method with a literature study approach. This study uses Henry Bernstein's theory of agrarian political economy. Data collection was carried out through secondary data sourced from books, journals, the internet, official documents related to village government and agricultural development. Data analysis used the interactive model Miles, Huberman and Saldana. The scope of this research is limited to village government intervention in the planning and implementation of agricultural development. The findings in this study are that the change in the system from centralization to decentralization has also changed the planning of agricultural development programs in villages that are more decentralized, participatory between the community and the village government. The recommendations/implications of these findings are expected to be able to contribute findings/ideas to studies of rural development in Indonesia, particularly the role of village governments in agricultural development and a political economy perspective in agricultural development to alleviate poverty, food security, and increase the income of people in rural areas. In addition, recommendations for village government intervention in development that are more pro-poor in rural areas.